The role of aerobic fitness and exercise intensity on endurance performance in uncompensable heat stress conditions - Périard, J. D.; Caillaud, C.; Thompson, M. W. (European Journal of Applied Physiology, 2012)
The aim of this study was to examine the influence of aerobic fitness and exercise intensity on the development of thermal and cardiovascular strain in uncompensable heat stress conditions. In three separate trials, eight aerobically trained and eight untrained subjects cycled to exhaustion at 60% (H60%) and 75% (H75%) of maximal oxygen uptake [Formula: see text] in 40°C conditions, and for 60 min at 60% [Formula: see text] in 18°C conditions (CON). Training status had no influence on time to exhaustion between trained (61 ± 10 and 31 ± 9 min) and untrained (58 ± 12 and 26 ± 10 min) subjects (H60% and H75%, respectively). Rectal temperature at exhaustion was also not significantly different between trained (39.8 ± 0.3, 39.3 ± 0.6 and 38.2 ± 0.3°C) and untrained (39.4 ± 0.5, 38.8 ± 0.5 and 38.2 ± 0.4°C) subjects, but was different between trials (H60%, H75% and CON, respectively; P < 0.01). However, because exercise was terminated on reaching the ethics approved rectal temperature limit in four trained subjects in the H60% trial and two in the H75% trial, it is speculated that increased rectal temperature may have further occurred in this cohort. Nonetheless, exhaustion occurred >96% of maximum heart rate in both cohorts and was accompanied by significant declines in stroke volume (15-26%), cardiac output (5-10%) and mean arterial pressure (9-13%) (P < 0.05). The increase in cardiovascular strain appears to represent the foremost factor precipitating fatigue during moderate and high intensity aerobic exercise in the heat in both trained and untrained subjects.